2023
DOI: 10.1177/00469580231155988
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Impact of New Health Price Transparency Policies

Abstract: This analysis investigates and scores the impact of new health price transparency rules. Using a set of novel data sources, we estimate substantial savings are possible following the implementation of the insurer price transparency rule. Specifically, we estimate annual savings to consumers, employers, and insurers by 2025, assuming a robust set of tools to allow consumers to purchase medical services. We matched claims with 70 HHS defined shoppable services by CPT and DRG codes and replaced them with an estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…This is true for all services provided including lab-tests, pharmaceuticals, medical devices, provider pay, and hospital reimbursement. The Hospital Price Transparency rule went into effect on 1 January 2021, with studies such as Parente’s, estimating annual savings to consumers, employers, and insurers by 2025 [ 6 ]. The concept of this policy started during George W. Bush’s presidency (2001-2009) with the goal for Americans to note significant savings in their health expenses, having foreknowledge of price-of-care ahead of time, and the opportunity to choose among cost-effective options.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is true for all services provided including lab-tests, pharmaceuticals, medical devices, provider pay, and hospital reimbursement. The Hospital Price Transparency rule went into effect on 1 January 2021, with studies such as Parente’s, estimating annual savings to consumers, employers, and insurers by 2025 [ 6 ]. The concept of this policy started during George W. Bush’s presidency (2001-2009) with the goal for Americans to note significant savings in their health expenses, having foreknowledge of price-of-care ahead of time, and the opportunity to choose among cost-effective options.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the barriers to price transparency, the benefits of price transparency drive the effort of its own expansion. A study reported that price transparency may yield between $17.6 and $80.7 billion in savings for patients, employers, and health plans by 2025 [ 6 ]. Benefits for patients include no surprise medical bills, ease to compare and choose providers, and more affordable healthcare services.…”
Section: Introductionmentioning
confidence: 99%
“…Given the novelty and scope of the price transparency rule change, a full analysis of the outcomes of the price transparency rule change will require years of data. 52 Other issues confound the goal of a robust, unbiased academic study. In addition to lawsuits, low initial compliance with the rule change and the lack of national data before the rule change are 2 additional obstacles.…”
Section: Assessment Of Health Care Price Transparency Literaturementioning
confidence: 99%
“…Parente used an upper bound analysis to estimate the impact of the price transparency rule for the commercial population by 2025 for income level, region, and state. 52 Using the 40% reduction in expenditures for “shoppable” services by shifting from negotiated commercial prices to cash prices suggested by the analysis from Lawrence Van Horn et al 54 —the same estimate used by the White House and HHS in 2019—Parente estimated the overall impact of price transparency for the commercial population in 2025 to be as high as $80.1 billion. 52 The analysis notably projected greater percent savings for low income beneficiaries at or below 137% of the Federal Poverty Line and variation across regions and states.…”
Section: Assessment Of Health Care Price Transparency Literaturementioning
confidence: 99%
See 1 more Smart Citation